CORPUS-BASED ANALYSIS: COLLOCATION OF NETIZENS’ WORDS IN INDONESIAN NEWS IN 2020 - Sumiyati, Neng; Fauziyah, Ely; Basid, Abdul (Annual International Conferences on Language, Literature, and Media; Vol 4 (2022): The 4th Annual International Conference on Language, Literature and MediaDO - 10.18860/aicollim.v4i1.1947, 2022)
Netizens or internet citizens are defined as people who are active in online communities by being involved in several online forums or social media. In online media in Indonesia, netizens are often referred to as a group of the most righteous. This term is included in word collocation or word matching related to netizens. This study aims to describe the collocation of netizen words in Indonesian news in 2020. This research is a mixed method study. The primary data source of this study is news data contained in the corpus, namely Leipzig Corpora Collection. The results of this corpus-based research found that there are two types of collocations of netizen words in the Indonesian news in 2020. First, collocation of noun + adjective consists of the words curious, excited, very excited, envious, furious, amazed, excited, suspicious, concerned, and worried. Second, adjective + noun collocation consists of many, few, excited, angry, exciting, evil, negative, crowded, funny, furious, suddenly, excited, funny, surprised.